Religious appeals in power politics - Henne, Peter (Religion and conflict (Cornell University Press), 2023)
"This book explores how states appeal to religion as part of international power politics, with particular focus on Saudi Arabia, the United States, and Russia. It argues that these appeals have major impacts on international relations, but rarely are the effects intended by states wielding them"--